1989
DOI: 10.1093/brain/112.1.233
|View full text |Cite
|
Sign up to set email alerts
|

The Bereitschaftspotential Is Abnormal in Parkinson's Disease

Abstract: The average Bereitschaftspotential (BP) preceding a rapid, self-paced voluntary extension movement of the index finger was recorded from 6 scalp locations in 14 patients with Parkinson's disease who had been withdrawn from their normal drug therapy for at least 12 h before testing. The amplitude of the potential was measured at the peak negativity (N1) and 650 ms prior to this (NS1), and compared with that recorded in a group of 12 age-matched control subjects. The N1 amplitude was the same as in the normals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
106
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(120 citation statements)
references
References 0 publications
12
106
1
1
Order By: Relevance
“…Previous research with MRCPs on pre-frontal lobe patients (Singh and Knight, 1990) and PD patients (Dick et al, 1989;Filipovic et al, 1997) demonstrated reduced BP amplitudes, indicating diminished preparatory activity in the SMA. As stated above, this structure determines the earliest amplitude of the MRCP (Toma et al, 2002), an origin confirmed by the present study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous research with MRCPs on pre-frontal lobe patients (Singh and Knight, 1990) and PD patients (Dick et al, 1989;Filipovic et al, 1997) demonstrated reduced BP amplitudes, indicating diminished preparatory activity in the SMA. As stated above, this structure determines the earliest amplitude of the MRCP (Toma et al, 2002), an origin confirmed by the present study.…”
Section: Discussionmentioning
confidence: 81%
“…However, it should also be observed that this similar deficit may have different origins in the two types of patients. In PD patients, the reduction of the BP component is thought to result from inadequate basal ganglia activation of SMA (Dick et al, 1989); this is also confirmed by functional MRI studies (Sabatini et al, 2000). In fact, it is well known that the basal ganglia provide a major source of afferent input to this structure.…”
Section: Discussionmentioning
confidence: 85%
“…Studies employing movement-related potentials in Parkinson's disease have mainly concerned investigations of the readiness potential (RP) (Deecke et al, 1977;Barrett et al, 1986ft;Dick et al, 1987Dick et al, ,1989Simpson and Khuraibet, 1987;Tarkka et al, 1990;Feve et al, 1992). The RP is a slowly rising potential of negative polarity with an onset between 1000 and 2000 ms before movement-onset.…”
Section: Introductionmentioning
confidence: 99%
“…The hypoactive DLPFC may compromise motor activity which reacts to external cues (Jahanshahi et al, 1995). The difficulty in self-initiated motor activity may arise from the impaired activity in the SMA and mesial-frontal areas (Jahanshahi et al, 1995;Playford et al, 1992) as hypo-activity in the SMA correlates with a reduced early component of the Bereitschaftspotential (Dick et al, 1989;Ikeda et al, 1997;Jahanshahi et al, 1995). Clinical improvement with dopaminergic substitution parallels the increase in SMA activity Rascol et al, 1992), while the hyperactivity in the lateral pre-motor and motor cortex diminishes (Haslinger et al, 2001).…”
Section: Pathophysiology Of Parkinson's Diseasementioning
confidence: 99%
“…The rationale for SMA-stimulation arises from its role in self-initiated movements which are impaired in PD (Dick et al, 1989;Ikeda et al, 1997;Jahanshahi et al, 1995). Based on the current studies, there is no evidence for therapeutic efficacy of low-or high-frequency rTMS of the SMA or the dorsal premotor cortex (dPMC) (Lefaucheur et al, 2014).…”
Section: Therapeutic Studies Of Non-invasive Brain Stimulation In Parmentioning
confidence: 99%